Hydro-geomortphological evolution analysis of a cliff - Reale, Ferdinando; Cuomo, Albina; Guida, Domenico; Dentale, Fabio; Di Leo, Angela; Pugliese Carratelli, Eugenio (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value=""1":2,"2":"The paper illustrates a mid-term geomorphological evolution analysis of the cliff called “Ripe Rosse”, one of the most important rocky coast geosite in the Cilento, Vallo di Diano and Alburni UNESCO Global Geopark. Specifically, the study aims to define the main geological and geomorphological characteristics of the areas in question. High coasts are usually the result of a very long evolution (thousands or even hundreds of thousands of years). This type of high coast is particular, it follows an evolution model called “slope-over-wall”. During the last decades, frequent and high-intensity landslide events have induced a significant increase in the risk especially along the unique state road connecting all touristic villages in Southern Cilento Coastland. In particular, in order to better identify integrated strategies to both preserve the geosite and prevent road damages, the geomorphological study has been supported by orientated numerical engineering modelling SCAPE (Soft Cliff And Platform Erosion). The application of the numerical model has given promising results on how the cliff will retreat in the next 500 years and therefore on how to mitigate the risk according to special value of the site."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The paper illustrates a mid-term geomorphological evolution analysis of the cliff called “Ripe Rosse”, one of the most important rocky coast geosite in the Cilento, Vallo di Diano and Alburni UNESCO Global Geopark. Specifically, the study aims to define the main geological and geomorphological characteristics of the areas in question. High coasts are usually the result of a very long evolution (thousands or even hundreds of thousands of years). This type of high coast is particular, it follows an evolution model called “slope-over-wall”. During the last decades, frequent and high-intensity landslide events have induced a significant increase in the risk especially along the unique state road connecting all touristic villages in Southern Cilento Coastland. In particular, in order to better identify integrated strategies to both preserve the geosite and prevent road damages, the geomorphological study has been supported by orientated numerical engineering modelling SCAPE (Soft Cliff And Platform Erosion). The application of the numerical model has given promising results on how the cliff will retreat in the next 500 years and therefore on how to mitigate the risk according to special value of the site.